West Nile Virus Challenge Alters the Transcription Profiles of Innate Immune Genes in Rabbit Peripheral Blood Mononuclear Cells - Uddin, Muhammad J.; Suen, Willy W.; Prow, Natalie A.; Hall, Roy A.; Bielefeldt-Ohmann, Helle (Frontiers in Veterinary Science, 2015)
The peripheral innate immune response to West Nile virus (WNV) is crucial for control of virus spread to the central nervous system. Therefore, transcriptomes encoding the innate immune response proteins against WNV were investigated in peripheral blood mononuclear cells (PBMCs) of New Zealand White rabbits, a recently established novel rabbit model for WNV pathogenesis studies. PBMCs were challenged with an Australian WNV strain, WNVNSW2011, in vitro, and mRNA expression of selected immune response genes were quantified at 2-, 6-, 12-, and 24-h post-infection (pi) using qRT-PCR. Compared to mock-inoculated PBMCs, WNV-stimulated PBMCs expressed high levels of interferon (IFN) alpha (IFNA), gamma (IFNG), IL6, IL12, IL22, CXCL10, and pentraxin 3 (PTX3) mRNA. Likewise, TLR1, 2, 3, 4, 6, and 10 mRNA became up-regulated with the highest expression seen for TLR3, 4, and 6. TLRs-signaling downstream genes (MyD88, STAT1, TRAF3, IRF7, and IRF9) subsequently became up-regulated. The high expression of IFNs, TLR3, TLR4, TRAF3, STAT1, IRF7, and IRF9 are in accordance with antiviral activities, while expression of TNFA, HO1, iNOS, caspase 3, and caspase 9 transcripts suggests the involvement of oxidative stress and apoptosis in WNV-stimulated rabbit PBMCs, respectively. The level of WNVNSW2011 RNA increased at 24-h pi in PBMCs challenged with virus in vitro compared to input virus. The expression dynamics of selected genes were validated in PBMCs from rabbits experimentally infected with WNV in vivo. Higher expression of IFNA, IFN beta (IFNB), IFNG, TNFA, IL6, IL22, PTX3, TLR3 and TLR4, IRF7, IRF9, STST1, TRAF3, caspase 3, and caspase 9 were seen in PBMCs from WNV-infected rabbits on day 3 post-intradermal virus inoculation compared to PBMCs from uninfected control rabbits. This study highlights the array of cytokines and TLRs involved in the host innate immune response to WNV in the rabbit leukocytes and suggests that these cells may be a useful in vitro model for WNV infection study.